A critical study of Acts 6:1–3 and its implications for political restructuring in Nigeria - Ngele, Omaka K. (HTS teologiese studies, 2019)
The nascent church in Jerusalem represented in Acts 6 verses 1–3 was promptly challenged by the problem of inequity and lack of fair play among the various stakeholders and such disaffection reached a situation of murmur and open agitation. This challenge to the apostles was a threat to the consolidation of the already established Christian community in Jerusalem and its spread to the whole world. Something must be done to arrest the situation or the Church runs the risk of disintegration. Having some moral lessons drawn from the pericope at the back of the mind, one notices that recently there has been a clamour by the different geopolitical groups in Nigeria to restructure the Nigerian political system. The clamour is based on the failed position of post-war federalism to give all parts of Nigeria’s pluralistic society a fair and equal representation which hitherto was meant to stop Nigeria from another civil war or the cry for cessation by one region or another. The church, as an impartial umpire in the art of politics, should, in the midst of the turmoil, serve as the conscience of the masses, pressing hard to the actualisation of the demands of the masses. The study, through historical-critical method of biblical scholarship with Form criticism, analysed that situation of agitation to inequality and gross misrepresentation in the book of Acts 6:1–3, pressing to offer vital lessons to Nigeria in her quest for political restructuring. It concluded by finding out that Nigeria’s pluralistic nature, when restructured, should be a catalyst for global vision attainment and sustainable development.